Highly Modular Protein Micropatterning Sheds Light on the Role of Clathrin-Mediated Endocytosis for the Quantitative Analysis of Protein-Protein Interactions in Live Cells - Lanzerstorfer, Peter (Biomolecules, 2020)
Protein micropatterning is a powerful tool for spatial arrangement of transmembrane and intracellular proteins in living cells. The restriction of one interaction partner (the bait, e.g., the receptor) in regular micropatterns within the plasma membrane and the monitoring of the lateral distribution of the bait’s interaction partner (the prey, e.g., the cytosolic downstream molecule) enables the in-depth examination of protein-protein interactions in a live cell context. This study reports on potential pitfalls and difficulties in data interpretation based on the enrichment of clathrin, which is a protein essential for clathrin-mediated receptor endocytosis. Using a highly modular micropatterning approach based on large-area micro-contact printing and streptavidin-biotin-mediated surface functionalization, clathrin was found to form internalization hotspots within the patterned areas, which, potentially, leads to unspecific bait/prey protein co-recruitment. We discuss the consequences of clathrin-coated pit formation on the quantitative analysis of relevant protein-protein interactions, describe controls and strategies to prevent the misinterpretation of data, and show that the use of DNA-based linker systems can lead to the improvement of the technical platform.